Injured nerves respond favorably to an integrated tension- and conduit-based regenerative strategy - Chuang, Ting-Hsien; Orozco, Elisabeth; Nam, Jae Jun; Vaz, Kenneth; Lovering, Richard M.; Shah, Sameer B. (Frontiers in Biomaterials Science, 2023)
Numerous synthetic, hybrid, and biological grafts and conduits have been deployed to facilitate axonal regeneration across peripheral nerve gaps. Though some strategies have showed promise, larger gaps continue to be an unsolved clinical challenge. Recent evidence suggests that tension-based strategies offer a promising alternative approach to nerve repair. However, whether and to what degree severed peripheral nerves tolerate and accommodate tension, especially in the critical early stages of intervention, is less clear. In this study, we tested the hypothesis that injured rat sciatic nerves accommodate strains of up to 20%, a deformation magnitude that exceeds oft-quoted thresholds for nerve damage. We also assessed the possibility of integrating tension with conduit-based approaches for nerve repair. There were no deficits in axonal, basal laminar, or extracellular matrix morphology with tension, though proximal and distal stumps of nerves in all experimental groups displayed abnormal morphology in proximity to the site of injury. Axons of stretched nerves successfully grew through guidance conduits into the distal stump within six weeks of repair, thus demonstrating the feasibility of combining tension- and conduit-based regenerative strategies.